PENGEMBANGAN MEDIA “SMART BOARDBOOK” BERBASIS AUGMENTED REALITY PADA TEMA 6 SUBTEMA 1 KELAS II SD NEGERI 104197 DESA KLAMBIR - Nurmayani Nurmayani; Liza Ayu Khairani (Universitas Negeri Medan, 2021)
The purpose of this study was to determine the feasibility and effectiveness of using Augmented Reality-based “Smart Boardbook” media. This research is a development research (Research and Development) which refers to the ADDIE development model which consists of 5 stages, namely the analysis, design, development, implementation, and evaluation stages. The research shows that the augmented reality-based “smart boardbook” media on the theme of 6 sub-theme 1 class II SD that was developed has been validated by a media expert validator in the first stage obtaining a feasibility percentage of 73.80% included in the “feasible” criteria and in stage II obtaining the results of the percentage of eligibility of 95.20% are included in the